The Sarcophaginae (Diptera: Sarcophagidae) of Southern South America. I. The species of Microcerella Macquart from the Patagonian Region - Mulieri, Pablo Ricardo; Mariluis, Juan Carlos; Patitucci, Luciano Damián; Olea, María Sofía (Zootaxa, 2015)
A revision is given of the species placed in the genus Microcerella Macquart, known from the southern extreme of South America, the so-called Patagonian Region. A new diagnosis of the genus is given on the basis of the revision of a large number of Neotropical species. A total of 25 valid species are recognized in the region. Most of these (21 species) are divided into four species-groups on the basis of general groundplan of genitalia and external characters. Four new species are described, M. deliae sp. nov., M. holmbergi sp. nov., M. nataliae sp. nov. and M. paetoi sp. nov. One new synonymy is established: Austrohartigia shannoni Lopes as a new junior synonym of Microcerella spinosa (Hall), syn. nov. A lectotype is designated for Doringia subandina Blanchard [a junior synonym of Microcerella spinigena (Rondani)]. Two species are recorded from Argentina for the first time: M. chicoensis (Lopes) and M. engeli (Hall). Three nominal species were not examined and are treated as nomina dubia within Microcerella: M. apicalis (Townsend), M. rufomaculata Macquart and M. sarcophagina Thomson. An illustrated key is provided to the males of Patagonian species of Microcerella allowing for separation of 25 species. Additionally, a series of images of male genitalia based on color photography and illustrations is provided to aid in the identification of these species of Microcerella. Biological information is given for the species, where known.